Epidémies de Choléra en Afrique Sub-Saharienne: Revue documentaire de 2010 à 2016 - Ibrahim, Alkassoum Salifou; Mahamadou, Doutchi; Harouna, Amadou; Souleymane, Brah; Issifou, Djibo; Lamine, Ibrahim Mahaman; A., Lagaré; Eric, Adehossi; Joseph, Aka; Saidou, Mamadou (European Scientific Journal, ESJ, 2019)
Introduction: Cholera remains a major public health problem in many parts of the world and particularly in sub-Saharan African countries. The objective of this study is to review data on cholera epidemiology, risk, microbiological and disease control factors in sub-Saharan Africa from 2010 to 2016. Material and method: A literature review on cholera epidemics in sub-Saharan Africa from 2010 to 2016 was conducted using electronic databases from countries that have experienced epidemics. Annual cholera data for countries with outbreaks from 2010 to 2016 have been reported. Results: From 2010 through 2016, 35 of the 54 African countries have experienced cholera epidemics. An overall of 1268 outbreaks have been reported, of which 13.04% were recorded in Nigeria and 4.35% in Burundi. The number of cases reported was 801022 and 13232 deaths (overall CFR =1.65%). Vibrio cholerae O1 and O139 are the main etiological agents. The main risk factors are heavy rains, floods, contamination of water sources and lack ofsanitation. Conclusion: In addition to the suffering of patients, cholera outbreaks cause panic, disrupt economic and social structures and hinder the development of affected communities. Mobilization of the water, sanitation and hygiene sectors is essential to ensure the benefits of patient care and cholera vaccination. Introduction : Le choléra demeure un problème majeur de Santé Publique dans de nombreuses parties du monde et en particulier dans les pays d’Afrique subsaharienne. L’objectif de cette étude de faire une revue des donnéessur les épidémies de choléra, les facteurs de risques, microbiologiques et de lutte contre la maladie en Afrique sub-saharienne de 2010 à 2016. Materiels et méthode: Une revue de la littérature sur les épidémies de choléra en Afrique sub-saharienne de 2010 à 2016 a été conduite dans des banques de données ou bases de données et bibiothèques électroniques des pays ayant connu des épidémies. Les données annuelles de choléra dans les pays ayant connu des épidémies de 2010 à 2016 ont été rapportées. Résultats : Entre 2010 et 2016, 35 des 54 pays d'Afrique ont connu des épidémies de choléra. 1268 épisodes épidémiques ont été rapportés dont 13,04% au Nigeria et 4,35% au Burundi. Le nombre de cas notifiés était de 801022 dont 13232 décès (létalité globale =1,65%). Le Vibrio cholerae O1 et O139 sont les principaux agents étiologiques épidémiogènes. Les principaux facteurs de risques sont les pluies abondantes, les inondations, la contamination des sources d’eau et le manque d’assainissement. Conclusion : En dehors des souffrances éprouvées par les malades, les flambées de choléra provoquent la panique, désorganisent les structures économiques et sociales et freinent le développement des communautés touchées. Cependant, la mobilisation des secteurs de l’eau, de l’assainissement et de l’hygiène ainsi que le rensforcement des systemes de surveillance et riposte surtout au niveau transfrontalier sont des etapes essentielles pour la lutte contre les epidemies de cholera en Afrique subsaharienne.